THE ROLE OF PERCEIVED USABILITY, SATISFACTION, AND CUSTOMER TRUST IN DESIGN AND DEVELOPING USER LOYALTY EDUTECH WEBSITE - Michael Vinsent Djulianto; Ayouvi Poerna Wardhanie; Candraningrat Candraningrat (UNUSA Press, 2022)
Indonesia has experienced developments in the world of education from year to year, and some of these developments directly impact the quality of education in Indonesia. The highest ranking edutech startup belongs to Ruangguru, followed by Neliti, Duniailkom, Eduka System, Wardya College, and other startups. This research aims to find out how perceived usability, Satisfaction, and customer trust play a role in developing user loyalty on the Ruangguru edutech startup website. The data collection method will be used to distribute surveys through questionnaires to 106 respondents consisting of Ruangguru users, namely junior high school students. High school students have thrice used Ruangguru’s services and opened the Ruangguru website. This study uses statistical techniques Partial least square Structural Equation Modeling (PLS-SEM) in the data analysis process that is useful for determining the significance level of the relationship between research variables. Based on the research, it was found that there is a significant effect of perceived usability on customer trust, Satisfaction, and customer loyalty, as well as perceived usability and Satisfaction on customer loyalty. In contrast, customer trust does not significantly impact customer loyalty website edutech.